EFEKTIFITAS DAN BERFUNGSINYA HUKUM DALAM MASYARAKAT - Djaenab Djaenab (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2018)
The law effectiveness is an activity showing strategy to overcome problems generally, such as the comparison of the reality of law and idealism. There are four factors influencing the effectiveness of law and its functions, including: 1) the rules of the law, 2) the law enforcer, 3) facilities, 4) The Publics. The functioning law in the publics means that the law has rules as social control and tools of social changes. To maximize those functions, the publics’ compliance on the law will support the law existence to be applied its function in the publics.